"POST-POSTSTRUCTURALIST" OR PRELAPSARIAN? CULTURAL STUDIES AND THE NEW HISTORICISM - Brantlinger, Patrick (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
A comparison of New Historicism and Cultural Studies as contemporary theoretical approaches to the problem of cultural analysis.